The effect of high-energy environments on the structure of laccase-polymerized poly(catechol) - Jing Su (2018)
The laccase polymerization of catechol was performed using different reactors namely a water bath (WB), an ultrasonic bath (US) and a high-pressure homogenizer (HPH). The total content of free OH and the MALDI-TOF spectra of polymers obtained demonstrated that reactions are favored in the presence of high-energy environments. Higher conversion yields and polymerization degrees (DP) were obtained after polymerization using US or HPH. Molecular dynamic simulation studies supported these findings by revealing a more open enzyme active site upon environments with high molecular agitation. The higher mass transport generated by US and HPH is the main feature responsible for a higher substrate accessibility to the enzyme which contributed to produce longer polymers.